Case Report: Acupuncture is an effective treatment for olfactory dysfunction in the post COVID-19 condition - Morita, Akira; Murakami, Aya; Uchihara, Takushu; Ohashi, Noriyuki; Ryu, Koichi; Watanabe, Yuki; Ochi, Sadayuki; Okudaira, Kazuho; Hirasaki, Yoshiro; Namiki, Takao (Frontiers in Neurology, 2022)
Olfactory dysfunction in the post COVID-19 condition reported worldwide are refractory for some patients. For this reason, appropriate treatment is desired. In this article, we describe two cases of olfactory dysfunction in the post-COVID-19 condition that was improved by traditional acupuncture treatment. By using the Yingxiang point (LI20), which is said to improve the sense of smell since ancient times, acupuncture treatment was performed 1–2 times a week in two patients about 6 and 7 months after the diagnosis of COVID-19. Acupuncture needles with a body length of 30 mm and a body diameter of 0.16 mm were inserted about 10 mm deep into the skin. We stimulated LI20 of the right and left sides until the patients felt the de qi sensation (acupuncture resonance), and left needles in the points for about 15 minutes. Immediately after the acupuncture treatment, the symptoms of olfactory dysfunction were alleviated, and the improvement in olfactory dysfunction lasted for 2–4 days. As the number of acupuncture treatments increased, the time until the flareup of olfactory dysfunction was prolonged, and the symptoms tended to decrease. In our experience, the acupuncture treatment was effective in a short period for treating residual olfactory dysfunction of the post-COVID-19 condition, suggesting that acupuncture may serve as an adjunct to modern medical treatment, and it may also be a new option for patients who are resistant to Western medical treatment or unable to continue treatment because of side effects. In conclusion, acupuncture may be a new option for patients who are resistant to modern medical treatment or who are unable to continue treatment because of side effects.